Li alloy-based non-volatile actuators - Noh, Myoung-Sub; Lee, Hyunseok; Song, Young Geun; Jung, Inki; Ning, Ruiguang; Paek, Sung Wook; Song, Hyun-Cheol; Baek, Seung-Hyub; Kang, Chong-Yun; Kim, Sangtae (ELSEVIER, 2019)
Conventional artificial muscles induce bending by aligning large-sized ions within the electrolyte upon bias application. Such design, alike many other actuator types, suffer from volatile actuation where the actuated position gets lost upon switch-off. Here, we develop a non-volatile artificial muscle with ion insertion electrode materials. Upon bias application, the inserted ions pose stress on the electrodes that sustain even after power shut-off. The demonstrated actuator consists of lithium germanide (LixGe) thin films deposited on both sides of a flexible polyimide (PI) substrate. The device exhibits 35.2 mm displacement when operated at 2 V and generates the blocking force of 0.67 mN. The observed stress and volume expansion reach 248 MPa and 8.2% for the 284 nm Li3Ge thin films, respectively. The actuated position is maintained against gravity with 12.1% decay in the actuated distance after 10 min. The novel actuator type proves the potential use of lithium insertion materials as actuation materials and shows that non-volatile actuation can be realized with ion-insertion electrodes.
Keywords: LITHIUM-ION BATTERY; MECHANICAL STRESSES; GERMANIUM; ELECTRODES; LITHIATION; DESIGN